The state of body iron in women anemic patients at Dr. Sardjito General Hospital - Setyawati Setyawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
Disorders resulting from body iron overload (hemosiderosis in reticgoendothelial cells or accumulation within parenchymal cells of the liver, heart and other organs) may octal- in patients who have undergone frequent blood transfusions or under other excessive iron therapy to treat the anemia. Therefore, every iron preparation especially by repeated parenteral route or blood transfusions must be accompanied by monitoring of body iron status.In the present study the most useful indirect measurement of ,body iron status, included serum ferritin (SF), serum iron (SI), total iron binding capacity (TIBC), transferin saturation (TS) and the erythrocyte, were studied in 34 women anemic patients at the Dr. Sardjito General Hospital.The results of the study are as follows: among 30 subjects with anemia caused by other than iron deficiency, included chronic renal diseases, inflammation or infection, hematologic and other organ malignancy, idiopathic thrombocytopenic purpura, the mean of SF level increased to 210,85ng/ml; but SI level (66,941g/d1) and TIBC (271, 07/Âµg/dl) showed no useful information about the state of iron stores, because its large biologic and analytic variability.In overall there was normal percentage of TS (25,58%), but among them 7 cases showed evidence of blood loss with TS less than normal, and erythrocyte indices within normal range.In 4 patients with uncomplicated iron deficiency anemia the mean of SF and 1'S were low (4,62ng/ml and 11,85% respectively), although SI only slightly decreased (38,7/tig/d1), and the TIBC was normal (340,3ffig/d1). The blood smears showed variation of size in the erythrocyte, with many smaller than normal and pale RBCs.It is concluded that ferritin serum measurement was the most sensitive and non invasive indicator for early stage of iron deficiency assessment. However, in fact no single indicator or, combination of indicators is ideal for the evaluation of body iron status in all clinical circumstances, because each indicator may be by other conditions such as infections, inflammations, liver, chronic, renal disease and malignancy.Key Words: anemia - serum ferritin - serum iron - total iron binding capacity - transferin saturation